Empowerment of education on orang asli community in Terengganu through knowledge transfer project. - Ramle, A.; Mohamad Hafis, A.S.; Lin, L.P; Sahar, H.; Asmawi, I. (2016)
Education is an important agenda in the design of human capital development in all countries. The Malaysian government has been focusing on the development of human capital not only to a certain group, but covers all levels of society, regardless of race, ethnicity, religion and race. In the context of Orang Asli peoples, various programs have been developed to ensure education among Orang Asli communities along with others in Malaysia. However, until now the educational achievement among Orang Asli peoples are still at a low level. A very serious problem involves the issue of dropouts, low grades in the exams, the problem of school absenteeism and problems related to the teaching-learning (Ramle Abdullah, 2011). Knowledge Transfer Project (KTP) have been implemented since 2013 to help alleviate the problem of education among Orang Asli especially in Terengganu. Among other objectives of the project are focused on increasing awareness of the responsibility and the importance of education among Orang Asli parents and students to reduce school absenteeism. The project is implemented by adopting organized intensive coaching classes to students, raise awareness and motivation to students, raise awareness and the importance of education to parents, school PIBG and empowering teaching and learning ecosystem. The results of the project showed increased attendance of students to the school, parents and local communities to better understand their responsibilities in managing their children's schooling. Some of them began to send their own children to school. Percentage of school attendance is increasing and students are better prepared for school.